2022
DOI: 10.3389/fcimb.2022.928503
|View full text |Cite
|
Sign up to set email alerts
|

Long Chain Fatty Acids and Virulence Repression in Intestinal Bacterial Pathogens

Abstract: When bacterial pathogens enter the gut, they encounter a complex milieu of signaling molecules and metabolites produced by host and microbial cells or derived from external sources such as the diet. This metabolomic landscape varies throughout the gut, thus establishing a biogeographical gradient of signals that may be sensed by pathogens and resident bacteria alike. Enteric bacterial pathogens have evolved elaborate mechanisms to appropriately regulate their virulence programs, which involves sensing and resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 90 publications
2
24
0
Order By: Relevance
“…A matter of concern is that patient carriage of or infection with another MDRO has been shown to increase the risk of CRE colonization more than 9-fold ( 42 ). As in this and other studies ( 35 , 36 ), CRE colonization is commonly associated with low SCFA levels. Moreover, these SCFAs serve to enhance the mucosal barrier and inhibit intestinal inflammation ( 30 32 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A matter of concern is that patient carriage of or infection with another MDRO has been shown to increase the risk of CRE colonization more than 9-fold ( 42 ). As in this and other studies ( 35 , 36 ), CRE colonization is commonly associated with low SCFA levels. Moreover, these SCFAs serve to enhance the mucosal barrier and inhibit intestinal inflammation ( 30 32 ).…”
Section: Discussionsupporting
confidence: 88%
“…These complicated activities involve microbe-microbe and microbe-host interactions, which include complex bacterial networks, the host immune system, and mucus and intestinal epithelial barrier integrity. A number of studies ( 30 32 , 35 , 36 ) have concluded that butyrate is able to recover barrier function through the positive regulation of the expression of claudin-1, ZO-1, and occludin in cdx2-transformed IEC-6 cells (cdx2-IEC) and Caco-2 cells, resulting in increased transepithelial electrical resistance. Thus, we conclude that, to a certain extent, lower SCFA levels were probably associated with downregulated TJ proteins in CRKP-colonized mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results imply that as Salmonella moves from the ileum toward environments with lower concentrations of formic acid, the invasion-rescuing effect of formic acid is lost. As the cecum and the colon have lower formic acid and higher fatty acid concentrations ( 14 ), the sequential exposure to these chemical cues may be utilized by Salmonella as a signal to switch from induction to repression of invasion. To test this hypothesis, we analyzed invasion gene expression in Salmonella under various conditions, using a hilA :: luxCDABE reporter fusion.…”
Section: Resultsmentioning
confidence: 99%
“…Bile functions by disrupting the HilD-DNA complex and mediates rapid degradation of the protein, thus preventing invasion ( 9 ). Similarly, the invasion event is avoided in the large intestine by using short- and long-chain fatty acids (S/LCFA), produced by a vast native microbiota ( 14 ). Fatty acids such as the propionic and oleic acids function to prevent invasion by disrupting the DNA-binding ability of HilD ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%